Early hominins and paleoecology of the Koobi Fora Formation, Lake Turkana Basin, Kenya - Bobe, R; D'Oliveira Coelho, J; Carvalho, S; Leakey, M (Cambridge University Press, 2022)
The Koobi Fora Fm (Formation) east of Lake Turkana in northern Kenya is one of the most important paleoanthropological rock units in the world (Figure 26.1). Nearly 250 hominin specimens are documented from East Turkana, representing the species Australopithecus anamensis, A. afarensis, Paranthropus boisei, Homo rudolfensis, H. habilis, and H. erectus (or ergaster) (M.G. Leakey, 1970; R.E. Leakey, 1973, 1976; Day et al., 1976; M.G. Leakey and R.E. Leakey, 1978; Kimbel, 1988; Wood, 1991; M.G. Leakey et al., 1995, 2012; Spoor et al., 2007; Wood and Leakey, 2011). Spanning from about 4.3 Ma (million years ago) to about 0.7 Ma, the abundant paleontological and sedimentological records of the Koobi Fora Fm offers a rich picture of hominin evolution and paleoenvironments during the Pliocene and early Pleistocene. In this contribution we present a synthesis of previous paleoecological work at East Turkana and add new paleontological analyses relevant to understanding the ecology of early hominins.